An Indian Boy With a Novel Leukodystrophy: 4H Syndrome. (January 2014) - Jauhari, Prashant; Sahu, Jitendra Kumar; Singhi, Pratibha; Dayal, Devi; Khandelwal, N.
4H syndrome is a rare and distinct leukodystrophy characterized by hypomyelination, hypogonadotropic hypogonadism, and hypodontia. Detecting signs of pubertal growth failure and abnormal dentition offer the clues to the diagnosis. We present an Indian boy with this novel syndrome with previously unreported feature of bilateral undescended testes. We also provide a brief overview of all published cases.